Accounting Workbook for Peachtree 2004 - Ulmer, Donna (Cengage Learning, Inc, 2005)
Accounting Workbook for Peachtree 2004 primarily is used in conjunction with the Heintz/Parry College Accounting family of products as well as a stand-alone product. Brief (250-300 pages) and packaged with the most current academic version of Peachtree software. Accounting Workbook for Peachtree 2004 is a tutorial/problem solving approach allowing users a process/flow to follow which provides necessary reinforcement of key concepts with plenty of practice throughout. Peachtree screen captures and instructions for using the software are found throughout the workbook. In addition, there is a reference/resource section for quick and easy access to frequently asked questions about Peachtree. Peachtree teaches users how to set up a new company's books